Upaya Guru Aqidah Akhlak dalam Menanamkam Rasa Empati pada Siswa Kelas VIII di Madrasah Islamiyah Belawan Kota Medan - Hadi, Syaiful; Sri Lestari; Rohmatulloh (UNISAN JURNAL, 2025)
This study aims to describe the efforts of Aqidah Akhlak teachers in fostering a sense of empathy among eighth-grade students at Madrasah Islamiyah Belawan, Medan City, during the 2024/2025 academic year. Empathy is one of the essential moral values in shaping students’ character. Through empathy, students are expected to understand others’ feelings, appreciate differences, and develop attitudes of helpfulness and tolerance in everyday life. However, observations at school show that some students still lack social awareness—such as being indifferent toward peers in difficulty, easily engaging in conflicts, and struggling to manage emotions effectively. Therefore, the role of Aqidah Akhlak teachers is crucial in cultivating empathy through learning activities and exemplary behavior within the school environment. This research employed a qualitative descriptive approach with research subjects consisting of Aqidah Akhlak teachers and eighth-grade students of Madrasah Islamiyah Belawan. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes three stages: data reduction, data display, and conclusion drawing. The findings reveal that Aqidah Akhlak teachers implement several strategies to instill empathy, including: (1) direct teaching, by integrating the value of empathy into moral lessons related to interpersonal ethics; (2) exemplary behavior (uswah hasanah) demonstrated in daily school interactions; (3) habit-forming activities, such as sharing with peers in need and engaging in school-based social activities; and (4) spiritual guidance, emphasizing that empathy is part of Allah’s command and the moral example of Prophet Muhammad (peace be upon him). Supporting factors include the school’s religious environment and cooperation among teachers, while inhibiting factors involve external environmental influences and low self-control among certain students. The study concludes that the role of Aqidah Akhlak teachers is highly strategic in cultivating students’ empathy through integrated learning approaches, exemplary conduct, and social habituation. The practice of empathy not only shapes students’ spiritual and moral character but also fosters a harmonious, tolerant, and respectful school climate.